Inflammatory mechanisms in atherosclerosis - Wolf, D.; Stachon, P.; Bode, C.; Zirlik, A. (Hämostaseologie, 2014)
Throughout the last two decades inflammation has been recognized as the central mechanism underlying atherogenesis. A multitude of basic science work demonstrates the pivotal role of inflammatory processes during every step of atherosclerotic plaque formation: From initiation via propagation to complication.This review describes some of the key mechanisms involved with a particular focus on the diverse group of inflammatory cells and their subsets that distinctly contribute to atherogenic and anti-atherogenic phenomena. Furthermore, we summarize the controlling action of a tight network of co-stimulatory molecules and cytokines orchestrating the inflammatory and anti-inflammatory effector functions. Finally, the current status of clinical trials evaluating anti-inflammatory/ immune-modulatory treatment strategies is summarized and an outlook for future therapeutic implications is provided.
Keywords: Atherosclerosis; inflammation; mechanisms; inflammatory cells; clinical trials